Reference in Formal Semantics and Natural Language: A Methodological Route - Boccuni, Francesca (Phenomenology and Mind, 2019)
In this paper, I will tackle the notion of reference of singular terms in the light of a classic analytic divide, i.e. whether its analysis, like the analysis of other basic notions, should be carried out in natural language or in the semantics of formal frameworks. I will incline toward the latter strategy, and consider reference in classical first-order logic as the simplest framework in which to investigate reference.